Kak wjele kompetentnych powědarjow dolnoserbšćiny jo w lěśe 2024? Pówoblicenje na zakłaźe aktualnych datow - Wojto, Till; Asmus, Sabine (Slavia Occidentalis, 2024)
Lower Sorbian is a Slavic language that has become almost extinct. As is the case of Upper Sorbian, there are no academic estimations of the current number of speakers of Lower Sorbian. Many German-language publications, including texts published by governmental institutions, overestimate the numbers of Lower Sorbian speakers, they are outdated or simply wrong. The authors take an innovative approach, initially defining a competent speaker of a minority language, and finally coming up with an estimation of the number of competent speakers of Lower Sorbian in 2024 based on latest data.